‘Grew up with a silver spoon in my mouth, but it ended up the nose’: the stigma and labelling of injection drug use in an affluent beachside community - Dertadian, George Christopher (Critical criminology, 2023)
Criminological scholarship has long grappled with the roles that stigma and labelling play in drug use in disadvantaged communities. While stigma leads to marginalisation, less is known about the way stigma impacts the structurally advantaged, or those from communities of relative affluence. Our research involved fieldwork and 18 qualitative interviews with people who inject drugs in the affluent coastal community of Sydney’s Northern Beaches. We find that even when people occupy the ‘ideal’ class position, internalised stigma was present, but did not readily translate into labels involving a criminal self-concept. We also found that while the capacity to resist crime-related labelling processes and other forms of state intervention were limited by social positionality, some participants still had to contend with intersecting forms of gendered and racialized stigma. However, for white male participants, their status and that of the area were experienced as protective of their criminalisation, actively limiting criminal labelling processes.